Kingdom without borders : the untold story of global Christianity - Adeney, Miriam, 1945- (Downers Grove, Ill. : IVP Books, 2009)
Adeney pulls back the veil on real Christians around the world--their faith, their hardships, their triumphs, and their failures--and shares the inspiring and challenging story of a kingdom that knows no borders.
Introduction: what I learned from Filipinos -- These are my people -- The elephant in the room : Jesus' people in China -- Word -- Pulsating passion : Jesus' people in Latin America -- Spirit -- Axis of hope : Jesus' people in the Muslim world -- Catastrophe -- Mystic servants : Jesus' people in the Hindu world -- Song -- When you go through fire : Jesus' people in Africa -- Way of the cross -- Way of life.
Includes bibliographical references.
Keywords: Christianity -- 21st century; Church history -- 21st century